Low doses of thymoquinone protect isolated human blood cells from TiO2 nanoparticles induced oxidative stress, hemolysis, cytotoxicity, DNA damage and collapse of mitochondrial activity - Mohammad Rafiq Wani; G.G. Hammad Ahmad Shadab (Elsevier, 2021)
Background: Due to extensive uses of titanium dioxide nanoparticles (TiO2 NPs) in food items, paints, cosmetics and other commonly used products, exposure to humans and environment is inevitable which has raised concerns regarding their toxic potential. Since NPs induce toxicity by generating oxidative stress, such toxicity can be prevented by antioxidants. Even though various antioxidants have been investigated for their protective effect, an effective chemo-protectant that can counteract the toxicity of TiO2 NPs is still elusive. Purpose: The purpose of this study was to determine potential adverse effects of TiO2 NPs in isolated human blood cells and to explore whether thymoquinone (TQ), a potent antioxidant, can protect against TiO2 NPs induced toxicity. Methods: Fresh blood was taken from volunteers with their informed consent and blood cells (erythrocytes and lymphocytes) isolated and treated with TiO2 NPs in vitro in the absence and presence of TQ and incubated for 3 h. Hemolysis and oxidative stress markers were determined in the erythrocytes while lymphocytes were tested for NP cytotoxicity by MTT assay, DNA damage by comet assay and effects on mitochondrial function by determining mitochondrial membrane potential and ADP/ATP ratio. Results: In samples treated with NPs alone, a statistically significant increase in the levels of hemolysis, reactive oxygen species, hydrogen peroxide and lipid peroxidation, together with a statistically significant decrease in the activity of antioxidants (catalase, superoxide dismutase and glutathione) was observed in erythrocytes, indicating oxidative stress occurred in these cells. In the lymphocytes treated with NPs only, MTT assay revealed cytotoxicity while Comet assay revealed DNA damage, besides collapse of mitochondrial membrane potential and increase in ADP/ATP ratio were also observed. However, in samples co-treated with low doses of antioxidant thymoquinone (TQ), TiO2 NPs induced changes were mitigated, indicating its antioxidant activity, but at higher doses, TQ showed pro-oxidant activity causing an increase in TiO2 NPs induced oxidative stress and damaging DNA. Conclusion: TiO2 NPs can induce adverse effects in isolated human blood cells. It seems that TQ, in low doses, acts as antioxidant and can be used as a protective agent against TiO2 NPs induced toxicity, but at higher doses, TQ becomes pro-oxidant.